PENGALAMAN KONSUMEN TERHADAP LAYANAN GOJEK DI KOTA JAKARTA: STUDI KUALITATIF DESKRIPTIF - Gunawan Wiradharma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Gojek is the first application for ordering taxibike in Indonesia. The existence of Gojek supports people’s lifestyle that always want to make all things easy and practical. The purpose of this research is to understand customer’s expirience with Gojek’s service in Jakarta. Research methods are used qualitative methods. Data is collected by observation and depth interview with 5 Gojek users. From each interviewed respondents were satisfied with the use of applications Gojek, so until now they still rely on Gojek as one of the alternative means of transportation of their flagship motorcycle taxi online. Key words : Customer’s expirience, Gojek application, Gojek users.